A Review of Energy Management Systems for Smart Grids - (:unkn) unknown (IEEE, 2015)
Technology is advancing every day. These developments are accelerating the industrialization of energy. Electricity demand is rapidly increasing. Therefore, effective use of the available energy is a very important issue. Smart Grid allows the management of energy and real-time balance between electrical energy supply and demand sides. In this study, we investigate energy management systems for smart grids.
Keywords: energy management; smart grid